Kajian Umur Jalan Rel Berdasarkan Keausan dengan Metode dari AREA dan Perjana - Adi, Wahyu Tamtomo (Politeknik Perkeretaapian Indonesia Madiun, 2019)
Determination of the service life of rails is important to do in order to avoid fatal damage. The estimated service life of components can be reviewed based on wear factors. This paper tries to calculate and compare the service life based on the formula for calculating the wear of the rail with the AREMA method that uses the empirical formula from Hay and uses the PT KAI method. The results show varying values ​​for existing crossings in the Madiun operating area, according to railroad specifications, cross loads, and railroad geometry. However, it is not possible to oppose the existing road conditions because there are limited data on the results of testing of the railroad being operated.